Designing learning trajectory based on Qur’an and Hadith: A case of fractions at Madrasah Ibtidaiyah - Dewi Rosikhoh; Abdussakir Abdussakir; Fawad Ali; M Islahul Mukmin (International Journal of Trends in Mathematics Education Research, 2022)
Islamic-based educational institutions needed to internalize Qur’an and hadith in every lesson. Fractions were one of the main subjects of mathematics taught at the elementary school level. The purpose of the study was to design mathematics learning to fractions based on Qur’an and hadith at Madrasah Ibtidaiyah. This study used a qualitative research method with a design research approach of development research type. The results of the study revealed that a learning design could be implemented with a scientific learning approach in fractions learning based on Qur’an and hadith. The verses of the Qur’an and hadith that explicitly mentioned fractional numbers were displayed at the observing stage. Each fractional number in the Qur’an and hadith was illustrated with a length model. Based on the fractional numbers mentioned in the observing stage, students were then directed to submit nutmeg questions in the questioning stage. The questions at the questioning stage were appropriate to the material, then discussed at the reasoning stage while still applying student-centered learning.